A Closer Look at the 'Global Reporting Initiative' Sustainability Reporting as a Tool to Implement Environmental and Social Policies: A Worldwide Sector Analysis. (11th July 2013) - del Mar Alonso‐Almeida, María; Llach, Josep; Marimon, Frederic
ABSTRACT This study analyses the worldwide diffusion of the Global Reporting Initiative's (GRI) Sustainability Report in all economic sectors from 1999 to 2011. The logistic curve model (s‐shaped curve) is used to assess the current situation on both a global scale and a local scale. Additionally, instability and concentration indices are used to analyse whether the diffusion process developed in a homogeneous manner across economic sectors. Although for different reasons, close attention has been paid to the two leading sectors worldwide: the financial and energy sectors. Findings suggest that the energy sector has adopted GRI reporting in an effort to be more sustainable as it is more visible, polluting, and international. On the other hand, the financial sector could regain market credibility and attract new investors, and GRI reporting could help it to construct a new identity defined by legitimate behaviours and an improved image. The paper concludes with some reflections on the usefulness of these reports and trends. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment